Pattern of Skeletal Metastasis in Breast Cancer Patients Attending INMAS, Rajshahi (Bangladesh Journal of Nuclear Medicine, 2019)
Breast cancer is the most common malignant tumor of females, the incidence increases with age. Bone is the most common site to which breast cancer metastasizes. Between 30% to 85% of patients with metastatic breast cancer develop bone metastases during the course of the disease. Bone scan is the most commonly used means of detecting bone metastasis; it visualizes increases in osteoblastic activity and skeletal vascularity. Many radio-pharmaceuticals (radionuclides) have been used in bone scan including technetium-99m bound to methylene diphosphonate (MDP). Published sensitivity and specificity rates of bone scan for diagnosis varies, with sensitivity ranging from 62% to 100% and specificity from 78% to 100%. However, bone scan is generally considered sensitive for detecting bone metastases on whole-body images.The aim of this study was to evaluate the pattern of distribution of skeletal metastases in patients with breast carcinoma by using Tc-99m MDP bone scan. A retrospective study was conducted on 245 consecutive female breast carcinoma patients irrespective of clinical staging, menopausal status and pre-operative / post- mastectomy status, referred for bone scan to Institute of Nuclear Medicine and Allied Sciences, Rajshahi from July 2015 to June 2017.  The mean age of the patients was 43.4 ± 13.8 years (mean ± SD) with range from 29 to 66 years. Bone scan was performed by an intravenous bolus injection of 20 mCi Tc99m-MDP. Bone phase images were taken at three hours after injection of the radiotracer. Out of 245 studied patients, 163 patients (66.53%) were negative for skeletal metastasis and 82 patients (33.47%) were positive for skeletal metastasis. Out of 82 patients with positive skeletal metastasis, 68 (82.93%) patients had multiple sites (two or more) and 14 (17.07%) patients had solitary site of bony involvement. Out of 68 patients with multiple sites of skeletal metastasis, highest number was noted in thoraco-lumbar spine (80.89%), followed by ribs including sternum and clavicle (57.35%), pelvic bones (47.06%), upper extremities including scapula (41.18%), lower extremities (33.82%), cervical spine (23.53%) and skull bone (8.82%). Among 14 patients with solitary skeletal metastasis, maximum number was noted in thoraco-lumbar spine (64.29%), followed by cervical spine (14.29%), pelvic bone (07.14%), ribs (07.14%) and sternum (07.14%). Skeletal metastases were  much more common in multiple sites than solitary lesion in breast cancer patients. Thoraco-lumbar spine was the most common site of involvement in both solitary and multiple lesions in our study. Axial skeleton was more commonly involved than the appendicular skeleton. Bone scan may pick up bone metastases up to 18 months earlier than conventional radiology, with an average lead of four months. 99m Tc- MDP bone scan is very cost effective in comparison to other imaging modalities (CT, MRI, and PET) and play a major role in early detection of skeletal metastasis in breast cancer patients.Bangladesh J. Nuclear Med. 21(1): 21-25, January 2018